Konstruierte Entzauberung: Überlegungen zur homiletischen Rezeption Walter Benjamins - Nierop, Jantine (International journal of practical theology, 2017)
Jürgen Ebach, Hans Martin Dober, and Albrecht Grözinger have argued for the appropriation of Walter Benjamin’s philosophy into homiletics. In this article, I first look at their proposal in all its diversity. I then turn to a striking shift in Benjamin’s philosophical development. Subsequently, I contend that the argument for such an appropriation of Benjamin can be sharpened even more by considering precisely this shift. The article concludes with my own proposal for appropriating Benjamin’s philosophy. It shows that Benjamin’s approach helps answer a central pastoral question in homiletics.